Structure of Sendai viral proteins in plasma membranes of virus-infected cells. - Bowen, H A (1981)
Purified plasma membranes attached to polycationic polyacrylamide beads by their external surface were isolated from BHK cells infected with Sendai virus. Each of the viral proteins could be identified in the membranes of infected cells. Proteolysis with trypsin, which digests only the cytoplasmic surface of these membranes (because the external surface is protected by its attachment to beads), revealed that the internal proteins, L, P, NP, and M, were present on the cytoplasmic surface of the membrane and that small segments of the viral envelope glycoproteins, HN and F0, were partially exposed on the cytoplasmic surface. Since the major portions of HN and F0 are known to be present on the external membrane surface, these glycoproteins are transmembrane proteins before Sendai virus budding in infected cells.